Concentration Banana Peel Liquid and Dose Chicken Manure Fertilizer toward growth Lettuce (Lactuca sativa L.) - Hastanah, Nurul; AM, Kartina; Fatmawaty, Andi Apriany; Rohmawati, Imas (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Lettuce is a vegetable plant originating from West Asia. Lettuce plants in Indonesia can be panted from the owlands to the highlands by considering selecting varieties. The high demind of Lettuce is not followed by an increase in production, low lettuce production is due to poor soil fertility and low levels of nutients in the soil due to excessive use of inorganic fertilizers and not paying attention to dosage. The use of organic fertilizer can increase soil fertility which is damaged by the use of inorganic fertilizer. The research was aimed to know effect of application the concentrstion of banana peel liquid based organic fertilizer and chicken manure fertilizer on the growth and yield of lettuce. The research was conducated in Sukajadi Barat Rt/Rw 001/005, Sukajadi Villager, Cibaliunh district, Pandeglang city, Banten. The method used Randomized Completely Block Design (RCBD) Concentration Banana peel liquid; 15%, 25%, and 35%. Dose chicken manure fertilizer; 71 g/polybag, 106 g/polybag, 141 g/polybag. The result research showed giving banana peel liquid influential real against all parameters except plant fresh weight. The giving chicken manure fertilizer influential real against all parameters except plant fresh weight. The conclusion of this research is the giving banana peel liquid at a concentration 25% gives the best results and chicken manure fertilizer at a dose 106 g/polybag gives the best results.